2003
DOI: 10.1007/bf02701991
|View full text |Cite
|
Sign up to set email alerts
|

Observations of wind and waves in the central Bay of Bengal during BOBMEX-99 and their effect on mixed layer depth variability due to forced mixing

Abstract: Time-series wind and wave measurements were carried out onboard INS Sagardhwani in the central Bay of Bengal during BOBMEX-99. Various other marine meteorological and oceanographic measurements relevant to monsoon studies were also collected simultaneously. The observed variations of wind and waves and the associated mixed layer depth (MLD) variability based on both temperature and density criteria at 3 hourly intervals are presented in this paper as a case study. At the time-series location (13 • N, 87 • E) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Two cells of very low density are found off the central east coast of India and northwest of the Andaman Islands, where freshwater discharges from the Krishna and Irrawady Rivers, respectively, enter the Bay [4] . Work has already been done on the entire oceans on geostrophic current using altimetry data and in the Indian Ocean [5][6][7][8] . During the 2004 tsunami, research on a satellite view of internal wave [9] found the effect of tsunami on marine ecosystem [1] .…”
Section: Densitymentioning
confidence: 99%
“…Two cells of very low density are found off the central east coast of India and northwest of the Andaman Islands, where freshwater discharges from the Krishna and Irrawady Rivers, respectively, enter the Bay [4] . Work has already been done on the entire oceans on geostrophic current using altimetry data and in the Indian Ocean [5][6][7][8] . During the 2004 tsunami, research on a satellite view of internal wave [9] found the effect of tsunami on marine ecosystem [1] .…”
Section: Densitymentioning
confidence: 99%